Evaluasi Kesesuaian Lahan Buah Pisang Kepok Didasarkan Agroklimat Dengan Pendekatan Sistem Informasi Geografis - Arham, Zainul (Prosiding SNATIKA Vol 01 (2011), 2011)
The era of computerization has opened up new horizons and paradigms in decision making and information dissemination. The data presented are processed in such a way and presented in a simplified form and as required. In accordance with the development of technology that has been achieved to date, particularly in the field of databases, information technology and remote sensing satellite technology, the need for storage, analysis and presentation of information more urgent. GIS is a technology that can provide a tool (tools) which are essential to store, manipulate, analyze and display natural conditions, such as agro-climatic conditions of an area with the help of spatial data and non-spatial data. Indonesia as a tropical country in Southeast Asia, has a diversity of Natural Resources (NR) biological various banana varieties. SDA-tropical humid agroecology and Human Resources (HR) and private farmers are quite large. This illustrates the substantial opportunities for development and increased production of bananas with the patterns of development that is integrated across sectors. The results of this research is agro-climatic suitability map banana plant in Bogor Regency, so that it can be used for planning and management of banana cultivation. Bogor Regency is dominated by conformity moderate (S2) so that the Bogor Regency is more suitable for banana cultivation in terms of climate, including rainfall ranges from 2900-3200 mm / year, temperatures reaching 23-25 degrees Celsius and humidity reaches 74 - 80%. Areas that fall into conformity is the Rumpin, Mount Sindur, Sawangan, Depok, Cimanggis, Gunung Putri, Bojong Gede and Cibinong, so the role of agro-climatic suitability on the suitability moderate (S2) for the banana crop was 78%. Key words: geographical information system (SIG), Banana (musa acuminata colla), Agroclimate and ModelBuilder